Музейні інновації та інтерактивність у теорії та практиці музейної справи - Банах, В. М. (Lviv Polytechnic Publishing House, 2016)
На прикладі практичного досвіду діяльності музейних установ України та світу зроблено спробу теоретично розмежувати музейні інновації та інтерактивність. Наведено конкретні приклади із практичної діяльності музеїв, спрямовану на запровадження у експозиційну, науково-фондову та освітню діяльність інноваційних та інтерактивних методик й практик. In this article it is attempted to carry out a theoretical distinction of museum innovations and interactivity on example of practical experience of museum institutions of Ukraine and the world. Museum innovations are considered in the broad and narrow contexts. The first one involves radical rethinking of traditional museum practices, of the places and the role of museums in society and culture, which contributes to the further evolution of the museum as a specific historical and cultural phenomenon. It also allows the museum to remain relevant in the context of contemporary social challenges. The concept of “innovations” in the narrow sense is reduced to the use of Internet resources, audiovisual and multimedia means in exposition and stock museum’s work. Primarily museum interactivity is considered in the context of scientific and educational activity of a museum. Interactivity of a museum scientific and educational work is visible in the differentiated approach to different categories of visitors, implementation of gaming and theatrical elements into guided tour, as well as in opportunities for visitors to have tactile access to exhibits, etc. In the article there are specific examples at practical activities of the museums that are aimed at the introduction of exposition, scientific, stock and educational activities as well as innovational and interactive techniques and practices.
Keywords: музей; інновації; інтерактивність; експозиція; фонди; маркетинг; мuseum; innovations; interactivity; exposition; funds; marketing; 069.5:2